2016
DOI: 10.1177/1476718x16664557
|View full text |Cite
|
Sign up to set email alerts
|

Block play and mathematics learning in preschool: The effects of building complexity, peer and teacher interactions in the block area, and replica play materials

Abstract: Block play has been included in early childhood classrooms for over a century, yet few studies have examined its effects on learning. Several previous investigations indicate that the complexity of block building is associated with math ability, but these studies were often conducted in adult-guided, laboratory settings. In the present investigation, the relationship of block play variables to both the complexity of block structures and math learning was studied in naturalistic free play settings. A total of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…One factor that appears to influence the increase in block building skills is that older children spend more time with blocks than younger children ( Clark et al, 1969 ), and the amount of time involved in block play has a positive effect on the complexity of block constructions ( Halford et al, 1998 ; Hanline et al, 2001 ), including more spatial dimensions ( Stiles-Davis, 1988 ; Stiles and Stern, 2001 ). Peer and teacher interactions in the block area also appear to promote block building performance ( Trawick-Smith et al, 2016 ), and systematic teaching of block building skills accounts in part for block structure complexity ( Casey et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…One factor that appears to influence the increase in block building skills is that older children spend more time with blocks than younger children ( Clark et al, 1969 ), and the amount of time involved in block play has a positive effect on the complexity of block constructions ( Halford et al, 1998 ; Hanline et al, 2001 ), including more spatial dimensions ( Stiles-Davis, 1988 ; Stiles and Stern, 2001 ). Peer and teacher interactions in the block area also appear to promote block building performance ( Trawick-Smith et al, 2016 ), and systematic teaching of block building skills accounts in part for block structure complexity ( Casey et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ramani (2012) found that children built larger, more complicated structures when they were engaged with a peer in a playful building activity compared to when they were presented with the same materials in an adult-directed and adult-structured activity. Similarly, social interaction among preschoolers was related to increased complexity of building with blocks ( Trawick-Smith et al, 2017 ). Although Park and Lee (2015) suggest that one of the advantages of working with a peer is benefiting from a higher-ability peer or one with higher social skills, even the illusion of working collaboratively has positive effects.…”
Section: Lessons From the Science Of Learningmentioning
confidence: 99%
“…This ability is especially important in the child’s using of blocks to copy preassembled models, as required in the MSCA, SBV, and WPPSI-IV and studied by Forman (1982). “Numeracy” has to do with the perception and computation of quantities in terms of numbers and the numbering system; the significant involvement of this capacity in block play is readily seen in the Block Structure Complexity Scoring Instrument (Trawick-Smith, Swaminathan, Baton, Danieluk, Marsh, & Szarwacki, 2017) and also highlighted by Phelps and Hanline (1999).…”
Section: A Proposed Model Of Block Building Skillsmentioning
confidence: 99%
“…Such a spatial focus is also highlighted in the BAS-R (Elliott et al, 1983) and WPPSI-IV (Wechsler, 2012). Next, "abstract reasoning" is highlighted in the MSCA (McCarthy, 1972) and SBV (Roid, 2003), which we think contributes to the overall structural complexity of the construction as assessed in the Three Methods of Evaluating the Complexity of Block Structures (Gregory & Whiren, 2003), BCSS (Phelps & Hanline, 1999;Hanline et al, 2001Hanline et al, , 2010, BPC (Ramani, 2012), and Block Structure Complexity Scoring Instrument (Trawick-Smith et al, 2017). "Representational thinking" points to the cognitive processes conducive to the building of mental models to represent some specific aspects of reality.…”
Section: A Proposed Model Of Block Building Skillsmentioning
confidence: 99%